Electrophilic fluorocyclization of allyl silanes. - Wilkinson, S; Lozano, O; Schuler, M; Pacheco, M; Salmon, R; Gouverneur, V (2009)
A refreshing cascade: General fluorocyclization reactions will breathe new life into the use of fluorinated hetero- and carbocycles as pharmaceuticals and agrochemicals. Allyl silanes have now been shown to undergo fluorinationcyclization with N-F reagents to give cis- and transsubstituted fluorinated heterocycles selectively (see scheme). The correct choice of silyl group was critical to prevent competitive fluorodesilylation. © 2009 Wiley-VCH Verlag GmbH and Co. KGaA.